Écologisation des arbres dans les agroforêts des Ghâts occidentaux (Inde) - Christelle Hinnewinkel; Sylvie Guillerme; Béatrice Moppert (Développement Durable et Territoires)
Inhabited for over 12,000 years, the forested Western Ghats landscapes are an interesting object of study for understanding how environmentalist discourse about the tree is currently articulated with the farmers’ discourse about the tree resource. Analysis of ways to conceive trees and their uses and the evolution of those conceptions, of the rules for access to the resource tree and of tree management practices was conducted based on 1 / field observations supplemented by surveys of farmers valuing the tree resource, and on 2 / study of reserved forest management plans, forest surveys and forest legislation. This work shows that farmers make a distinction in their agroforests between what they describe as “forest trees” on the one hand and as “their trees” on the other. The analysis of forest policy helps to understand that this way of qualifying the trees is the result of bringing forward the environmental agenda by the forestry administration, and of the integration of this agenda by the people who depend on tree resource in their daily lives. In the speech, the majority of farmers mobilizes the ecological argument in particular to justify the ban on cutting “forest trees”, but they do not forget social and economic values of those trees.